Analysis of Crime Data in the Limpopo Province - Kwabena A Kyei (Journal of Economics and Behavioral Studies, 2017)
South Africa has a very high rate of murders, assaults, rapes and other crimes compared to most countries. Most South Africans who immigrate to other countries cite crime as the major reason. Crime has become a concern for all, the police, private security industry, real estate developer, car manufacturers, businessmen, etc. There is a high demand for crime prevention; and this calls for a continuous use of new, advanced and reliable methods to prevent crime. How bad is the level of crime in Limpopo and what are the major crime types? This study uses secondary data from the 2011 Census conducted by Statistics South Africa; and tries to look at the composition of crime in the province and the variables that influence crime, in order to propose measures to tackle and minimize crime in the province. Multivariate statistical analysis has been employed, and the study shows that the following variables; the population size, number of households, youth unemployment, growth rate, and dependency ratio; have a positive influence in the occurrence of crime. The study recommends the slowing down of population growth rate, decrease in household size and the reduction of youth unemployment to curb crime in the province.